The effect of diarrheal disease on bivalent oral polio vaccine (bOPV) immune response in infants in Nepal. Issue 22 (11th May 2016) - Cardemil, Cristina V.; Estivariz, Concepcion; Shrestha, Laxman; Sherchand, Jeevan B.; Sharma, Arun; Gary, Howard E.; Oberste, M. Steven; Weldon, William C.; Bowen, Michael D.; Vinjé, Jan; Schluter, W. William; Anand, Abhijeet; et al.
Abstract: Background: A globally-coordinated phase out of all type 2 containing oral polio vaccine (OPV) is planned for April 2016 during which bivalent 1 + 3 OPV (bOPV) will replace trivalent OPV (tOPV) in routine immunization schedules and campaigns. Diarrhea impairs the immune response to tOPV, but the effect of diarrhea on bOPV is unknown. Methods: Infants aged 6 weeks to 11 months, who had received <3 doses of OPV and had mild-moderate diarrhea or no diarrhea, were recruited at five health facilities in Nepal. Neutralizing antibody titers to poliovirus types 1 and 3 were measured before and 28 days after bOPV administration. The effect of diarrhea and other factors on seroconversion or boosting in antibody titers to poliovirus was assessed by multivariable analysis. Results: Infants with diarrhea, versus those without diarrhea, had reduced response for poliovirus types 1 (56% [87/156] vs 66% [109/164]) and 3 (34% [70/209] vs 52% [122/236]). After adjusting for other factors, infants with diarrhea had significantly reduced response for type 3 (odds ratio [OR] = 0.44, 95% CI 0.29–0.68), as did infants with >5 loose stools per day (OR = 0.36, 95% CI 0.21–0.62). Conclusions: Diarrhea reduced the immune response to bOPV. Provision of additional doses of polio vaccine is necessary to maintain high population immunity in areas with high prevalence of diarrheal disease. Clinical trial registry: This study is registered at clinicaltrials.gov asNCT01559636 .